Genome Sequence of Aeromonas hydrophila Strain AH-3 (Serotype O34) - Forn-Cuní, Gabriel (Genome Announc, 2016)
Aeromonas hydrophila is an emerging pathogen of poikilothermic animals, from fish to mammals, including humans. Here, we report the whole-genome sequence of the A. hydrophila AH-3 strain, isolated from a fish farm goldfish septicemia outbreak in Spain, with a characterized polar and lateral flagellum glycosylation pattern.